(untitled) (International Journal of Engineering and Computer Science, 2023)
The Internet of Things (IoT) presents a wide range of issues and challenges. Security is a major concern for IoT technologies, applications, and networks. IoT’s research progress is discussed in this paper, which focuses on this primary feature of IoT and describes various security issues and concerns. The Internet of Things and the concept of edge computing have enabled many new IoT applications, including smart homes, intelligent transportation, pioneering health, smart grids, and smart energy. It also introduces a slew of unanticipated challenges to data security. Cybersecurity, edge computing, the Internet of Things, and artificial intelligence all present exciting new research and development prospects. There are many new threats and opportunities and this paper will focus on them.